Sedation methods for controlling fear and anxiety in Dentistry (Research, Society and Development, 2023)
The general objective of the study focuses on explaining in detail the different types of sedation in Dentistry. This is a narrative literature review, in which the study was developed by carrying out searches in the main health sciences databases, such as: PubMeD, Scielo and Lilacs. The search filters were applied to studies published between 2019 and 2023, in Portuguese and English, available electronically. The inclusion criteria were established for applied research, literature reviews, integrative and systematic reviews, meta-analyses, case reports, books and book chapters. The exclusion criteria involved studies that make up the gray literature, abstracts of annals, letters to the author and opinion articles. The searches carried out in the aforementioned databases totaled 38 studies, which were subjected to a careful analysis, using pre-established inclusion and exclusion criteria. The study selection stage involved reading the title, reading the summary, followed by reading the full content. It is concluded that sedation methods in dentistry play a crucial role in managing patient anxiety, facilitating dental care and improving communication between the professional and the patient.